The Transmission Mechanism of European Monetary Policy : Is There Heterogeneity? Is it Changing over Time? - Ciccarelli, Matteo (IMF Working Papers; Working Paper ;, 2002)
This paper investigates the transmission mechanism of monetary policy in the four largest euro area countries by means Bayesian estimation of dynamic econometric models. Based on pre-EMU evidence from Germany, France, Italy, and Spain, we show that: (i) there are differences in the timing of the effects of monetary policy on economic activity, but their cumulative impact after two years is rather homogeneous; (ii) the transmission mechanism seems to have changed over time in the run-up to EMU but its degree of heterogeneity has not decreased; (iii) the "European-wide" effects of monetary policy may have become faster in the second half of the 1990s. We interpret this evidence by conjecturing that the transmission mechanism of monetary policy had already become relatively homogenous in the second part of the 1990s.